Imaging via Correlation of X-Ray Fluorescence Photons - Trost, Fabian; Ayyer, Kartik; Prasciolu, Mauro; Fleckenstein, Holger; Barthelmess, Miriam; Yefanov, Oleksandr; Dresselhaus, J. Lukas; Li, Chufeng; Bait, Sasa; Carnis, Jerome; Wollweber, Tamme; Mall, Abhishek; et al. (Physical Review Letters, 2023)
We demonstrate that x-ray fluorescence emission, which cannot maintain a stationary interference pattern, can be used to obtain images of structures by recording photon-photon correlations in the manner of the stellar intensity interferometry of Hanbury Brown and Twiss. This is achieved utilizing femtosecond-duration pulses of a hard x-ray free-electron laser to generate the emission in exposures comparable to the coherence time of the fluorescence. Iterative phasing of the photon correlation map generated a model-free real-space image of the structure of the emitters. Since fluorescence can dominate coherent scattering, this may enable imaging uncrystallised macromolecules.
CRIS-Team Scopus Importer:2023-05-26